Pemberdayaan Masyarakat melalui Pelatihan Pengolahan Nugget Daging Ayam Kombinasi Buah Sukun pada Desa Lampisang Kabupaten Aceh Besar - Masyitah Masyitah; Devia Fitria; Rahmaya Rahmaya; Ahmad Hamim Damanik; Muhammad Rizki Fadhillah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Chicken Nuggets is a processed product made from ground meat with several additional ingredients and moulded in various shapes. Innovatio in the use of breadfruit which has nutrients in the form of carbohydrates, fiber, protein, vitamins, and so on so that this food product has the potential to be of choice materials in chiken nugget product. Meanwhile, Lampisang Village, Peukan Bada District, Aceh Besar Regency, as a location for Community Service activity. The activities carried out were counseling and demontration on chicken nuggets with addition buah sukun. From this activity it can beconcluded that the implementation through community service processing chicken meat with addition buah sukun into nuggets, service participants can increase their knowledge and skills in diversifikasi chicken meat. The implementation of the activity has been successful and has receiveda good response.